Análise do uso do recurso PROAP/CAPES nos programas de Pós-Graduação em química e física da UFES no período de 2010 a 2012 - Freitas, Levi Antonio Nunes de (2016)
It is known that public resources have been scarce, the management of publicresources is an essential tool which cause a positive impact on the society where the institution is located. According to this, the present study aimed on investigating and analyzing how PROAP/CAPES resource is invested in the program of Postgraduation studies of Chemistry and Physics between 2010 and 2012, promoting an analysis of the management of the programs surveyed.Specifically, the research sought to reveal the usual practice management planning these programs, difficulties in management and in the end the suggestions for improvement of this process. As an instrument of data collection, semi-structured questionnaires were used to gather information from those who are closely linked to related activities and encouraged by the resource. The survey found that despite the increasing volume of action for the programs, the results point to a lack and even ignorance of the resource, which compromise their efficient use. With the survey results, changes in order to optimize resource usage can be implemented by cooperating to that good management practices are observed